Kewenangan Berhak dan Kewenangan Bertindak Menurut Hukum Perdata Suatu Kajian Normatif - Sebastianus Nong Mario Zakaria; Agustinus Hedewata; Yossie M. Y. Jacob (Hakim, 2024)
The aim of this research is to find out the concepts of entitled authority and acting authority in civil law as well as the relevance and implications of regulating entitled authority and acting authority in civil law practice. The type of research used by the author is Normative Law research, the type of data used in this research is qualitative data. The data used in research is based on the relevance of the source data, namely primary and secondary data. The results of this research are that the results of the research show that Rightful Authority is defined as the authority of an individual or a legal entity to carry out a legal act in a community's social life which is considered valid because it constitutes his or her essence as a human being or individual or as a legal entity while the Authority to Act is defined as Special authority. The special authority referred to is authority that only applies to certain people and for certain legal actions, whereas the relevance and implications show that there is no relevance in regulating the authority to have rights and the authority to act in civil law. This is shown by cases that frequently occur. for example, early marriage.